The Effect of Accounting Information on Stock Price Predictions Through Fluctuation of Stock Price, Evidence From Indonesia - Tambun, Sihar; Murwaningsari, Etty; Mayangsari, Sekar (Journal of Accounting, Business and Finance Research, 2018)
This article describes the results of research on the effect of accounting information on the accuracy of analyst predictions, using stock price fluctuations as a mediation variable. Accounting information uses three measurements, i.e. changes in revenue, changes in net income before extraordinary (NIBE), and changes in debt. This accounting information is combined with market information such as stock price information. A sample of 54 issuers listed on the Indonesia Stock Exchange. The sample is selected using the purposive sampling method. The analytical method uses the ordinary least square estimation method with the data panel structure, to test for direct influence. For indirect effect test, used two least square methods with panel data structure. The tool that used in this analysis was Stata. The results show that changes in revenue have a significant impact on stock price fluctuations. Then, stock price fluctuations may mediate the effect of information on revenue changes on the precise prediction of analysts. This means that changes in revenue will be stronger influence on the accuracy of analyst predictions, if there is an increase in stock prices. For indirect influence, this study proves that changes in revenue affect the accuracy of analyst predictions, through fluctuations in stock prices.